A rectal ulcer caused by hydrogel spacer insertion: A case report and review of the literature - Sen Yagi; Moyu Kawano; Keitaro Kawasaki; Takatoshi Murakami; Jiro Miyaike; Shinya Furukawa (DEN Open)
Abstract A 75‐year‐old man presented with hematochezia. He had been diagnosed with prostate cancer (stage 1) 1 month previously and had undergone gold marker injection and hydrogel spacer insertion 3 weeks previously to prepare for radiotherapy. Hydrogel spacer insertion is a safe procedure that can prevent the side effects of radiotherapy for prostate cancer. A computed tomography evaluation identified a low‐density area that extended from the prostate to the rectal wall. Magnetic resonance imaging of the abdomen revealed the hydrogel spacer between the anterior rectal wall and prostate. A colonoscopy revealed an approximately 2 cm ulcer in the rectum. The patient was diagnosed with a rectal ulcer with bleeding caused by hydrogel spacer insertion. Conservative follow‐up was performed, and his condition improved over time. Radiotherapy for prostate cancer was initiated 4 months after hydrogel spacer insertion. The patient has not experienced any abdominal symptoms such as bloody stools since that time. Because the incidence of prostate cancer is increasing, the number of such cases is likely to increase in the future.